Business Enterprises Activities in Arms Industry Sector: International Law Overview - Bernhard Ruben Fritz Sumigar (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2020)
In the current era of Revolution Industry 4.0, the advance of technology is indeed influenced the rapid development of arms industry. This supported by the arms companies’ contribution in supplying weapons to the warring parties. Nevertheless, such indirect participation in armed conflicts is marred by serious violations of human rights and the law of armed conflicts. By virtue of this reasoning, this article is present to evaluate whether these arms companies are bound by international law. The author observed that there are certain provisions under International Humanitarian Law and International Human Rights Law that can be applied for mitigating, as well as preventing these companies for not conducting any activities with similar nature in the near future.